A â€œEXOCORTISâ€ E A SITUAÃ‡ÃƒO ATUAL DOS PORTA-ENXERTOS PARA CITRUS - Montenegro, Heitor W. S.; Salibe, Ary A. (REVISTA DE AGRICULTURA, 2016)
A â€œEXOCORTISâ€ E A SITUAÃ‡ÃƒO ATUAL DOS PORTA-ENXERTOS PARA CITRUS